The Role of Green Investment Policies in Promoting Economic Diversification in the Gulf Countries - Majid, Marenda Athallah Farras; Yafuz, Labiq; Fathullah, Abdusyahid Naufal; Bari, Tatsqif Abyani Fathul (Strata Social and Humanities Studies, 2025)
Gulf countries, including Saudi Arabia, the United Arab Emirates (UAE), and Qatar, face economic challenges due to their high dependence on oil and gas exports. To address oil price volatility and support the transition to a sustainable economy, they have implemented green investment policies as part of their economic diversification strategy. The study examines the effectiveness of green investment in boosting the growth of non-oil and gas economies through policies such as Saudi Vision 2030, UAE Net Zero 2050, and Qatar National Vision 2030. The results show that green investment has improved the region's economic competitiveness by attracting foreign direct investment (FDI), creating new industrial sectors, and accelerating innovation in renewable energy. Despite this, various challenges are still faced, including limited infrastructure, dependence on imported technology, and resistance from the oil and gas industry. In addition, geopolitical dynamics and fiscal policies that have not been fully supportive are obstacles to the implementation of green investment. The study confirms that green investment has the potential to become a key pillar in the economic diversification of Gulf countries if supported by a more structured strategy, research and development (R&D) capacity building, and incentive policies that encourage private sector involvement and international cooperation.